2016
DOI: 10.1117/1.jbo.21.6.066015
|View full text |Cite
|
Sign up to set email alerts
|

Polarization response of second-harmonic images for different collagen spatial distributions

Abstract: The response to polarization of second-harmonic generation (SHG) microscopy images of samples with different collagen distributions (quasialigned, partially organized, and nonorganized) has been analyzed. A linear decay relationship between the external arrangement and polarization sensitivity was found. SHG signal from nonorganized samples presented a large structural dispersion and a weak dependence with incident polarization. Polarization dependence is also associated with the internal organization of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
(45 reference statements)
2
14
0
2
Order By: Relevance
“…It is well known that SHG signal emerging from a sample is polarization dependent. Moreover, it has also been reported that the modulation of the SHG signal for linear polarization is maximized when the sample under study presents a quasiparallel external structure, that is DoI values >0.70 [12]. When the sample presents a lower external organization (i.e.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is well known that SHG signal emerging from a sample is polarization dependent. Moreover, it has also been reported that the modulation of the SHG signal for linear polarization is maximized when the sample under study presents a quasiparallel external structure, that is DoI values >0.70 [12]. When the sample presents a lower external organization (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…However the use of elliptical states might provide improved SHG signal and relevant information [16][17][18]. Whereas the dependence of quasi-parallel collagen structures and linear polarization is well understood (theoretical and experimentally), the combination of samples with non-regular arrangements and incident elliptical polarized light is still a topic of interest [12,19]. Moreover, some polarization parameters such as the dichroic ratio [12,20] or the anisotropy factor [21] have been defined taking into account only linear polarization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, el signo de  determina la forma de la distribución de intensidad: para valores negativos aparece un máximo secundario en torno al estado de polarización vertical [16].. En las muestras aquí utilizadas el tejido de escleral presenta valor positivo de , mientras que la córnea muestra una distribución de intensidad correspondiente a valores negativos de . Mapas de  para dichas muestras (derecha).…”
Section: Organización Interna Y Señal Shg Polariméticaunclassified
“…• Construcción de un modelo teórico para analizar la sensibilidad a la polarización de la señal SHG en colágeno tipo I, permitiendo obtener una expresión analítica para el cálculo de la organización interna o a escala molecular [15]. La comprobación experimental permitió obtener por primera vez la relación entre la organización interna y externa del colágeno [16]. La sensibilidad a la polarización fue propuesta como método de diagnóstico clínico de la patología corneal conocida como queratocono.…”
Section: Introductionunclassified